Evaluasi Luaran Klinis Terapi Antibiotik pada Pasien Community Acquired Pneumonia Anak Rawat Inap - Sabrina Handayani Tambun; Ika Puspitasari; Ida Safitri Laksanawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Community Acquired Pneumonia (CAP) is an infectious disease which is one of the main causes of child mortality in developing countries. The pattern of giving antibiotics at the hospital is usually still empirical. Inappropriate use of antibiotics may cause failure of therapy or bacterial resistance. This study aims to determine the empirical antibiotic rationality and the relationship of rationality to the clinical outcome of CAP-pediatric inpatients at RSUP. Dr. Sardjito Yogyakarta. The study conducted using a descriptive analytic method with a retrospective cohort design. The subjects were CAP-pediatric inpatients at RSUP. Dr. Sardjito Yogyakarta period 1 January-31 December 2018. The rationality of empirical antibiotics is evaluated using the Gyssens algorithm. The clinical outcome was either good or bad outcome according to the clinician stating in the medical record. Patient characteristics, empirical antibiotic therapy and rationality patterns were analyzed descriptively. The relationship between empirical antibiotic rationality and clinical outcome were evaluated using Chi square test. There were 73 patients who met the inclusion and exclusion criteria (132 empirical antibiotic regimens). Rational antibiotic therapy accounted 76.5% (category 0). Types of irrationality of antibiotic found were IIIB (5.3%) and IIA categories (18.2%). Chi-square analysis showed that empirical antibiotic rationality related to good clinical outcome of CAP children (p = 0.011; OR = 2.957; 95% CI = 1,263 - 6,923).